RETRACTED: The Impact of WebQuest-Based Sheltered Instruction on Improving Academic Writing Skills, Soft Skills, and Minimizing Writing Anxiety - Salem, Ashraf Atta Mohamed S. (Frontiers in Education, 2022)
WebQuest is an inquiry-oriented learning tool in which the majority of the information learners interact with, comes from Internet resources, according to Bernie Dodge, who conceived and named the concept (Dodge, 1997). Students are given a job and instructed to do it using Web resources. The current study explores the impact of learning in a sheltered Internet environment, “WebQuest,” on improving the academic writing skills of English for Academic Purposes (EAP) non-native English speakers. It also investigates the impact of using sheltered online instruction on improving the soft skills of EAP language learners. In addition, the study assesses the impact of sheltered online instruction on reducing the writing anxiety levels of writers in the International English Language Testing System (IELTS; Writing Task 1 and 2). To reach such end, three groups of EAP learners were selected to participate in the study adopting three learning styles: sheltered online instruction (the experimental group, 15 ESP university students), unsheltered online instruction (free Google search) (the first control group, 19 students), and sheltered offline instruction (the second control group, 20 students). Instruments used included a sample of the IELTS writing test, Brookings Soft Skills Rating Card, and Second Language Writing Anxiety Inventory (SLWAI). Sequential exploratory mixed method was used as it consists of both quantitative and qualitative data analyses for the elaborate explanation of results. Successive rounds of data analyses showed the plentiful gains of the EAP students in their academic writing skills and the level of their soft skills. It is also revealed that EAP students are not as anxious and reluctant to write as before. In addition, the analysis of the students’ responses to the semi-structured interview revealed that learning in sheltered Internet environments represents an interesting as well as motivating learning experience. Therefore, it is necessary for WebQuest to be implemented as a sheltered online instruction strategy in language learning and to design sheltered Internet environments other than WebQuest to improve the quality of the teaching process.